2018
DOI: 10.1108/bpmj-05-2017-0122
|View full text |Cite
|
Sign up to set email alerts
|

Business strategy modelling based on enterprise architecture: a state of the art review

Abstract: Purpose Enterprise architecture (EA) is a means of a high level of abstraction of a business’ levels which helps organise planning and taking better decisions. Evidence has shown that the scope of EA is not restricted to technology planning, but the lack of business strategy and processes is the most common problem of EA frameworks. Consequently, a challenge stems from the fact that the formulation of strategy should not be modelled separately but as a holistic approach. The purpose of this paper is to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 45 publications
0
57
0
1
Order By: Relevance
“…As it has already been stated, the aim of this paper is to examine the current state of corporate sustainability strategies and the decision-making process. Studies were identified using a three-phased literature review methodology, which was suggested by Webster and Watson (2002) [12], and has been previously used in the field of strategic management and Information Systems [13][14][15][16][17][18][19][20][21][22]. First, a search of the extant literature reviews was done to select the databases and keywords of the basic search.…”
Section: Methodsmentioning
confidence: 99%
“…As it has already been stated, the aim of this paper is to examine the current state of corporate sustainability strategies and the decision-making process. Studies were identified using a three-phased literature review methodology, which was suggested by Webster and Watson (2002) [12], and has been previously used in the field of strategic management and Information Systems [13][14][15][16][17][18][19][20][21][22]. First, a search of the extant literature reviews was done to select the databases and keywords of the basic search.…”
Section: Methodsmentioning
confidence: 99%
“…It also includes variables such as the alignment of IT strategy with the strategic plan of the organization, the education of top managers with regards to the importance of IT and the adaption of technology to strategic change [25,32,33,39,41,50,51]. The second one is solely preoccupied with the generation of new ideas on how to reengineer business process through IT [52]. At this point the understanding of both information needs through subunits, and the dispersion of data, application and other technologies throughout the firm so that a blueprint which will improve organizational processes could be developed, are all considered extremely important issues.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…EA comes into the picture here, as the authors discuss [27], by supporting organizations to govern their IT by traditional and IT strategies. A gap exists in the EA literature because strategy and governance are usually considered individually, without a deeper understanding of other related EA practices [9,32,37,39,45]. A growing trend in the EA literature is the discussion on the usage of strategic and governance practices such as strategic auditing, SWOT analysis, balanced score cards, and competitive advantage [13,39].…”
Section: Strategic Practicesmentioning
confidence: 99%
“…A growing trend in the EA literature is the discussion on the usage of strategic and governance practices such as strategic auditing, SWOT analysis, balanced score cards, and competitive advantage [13,39]. This shows that EA research is streamlining from being a computer and information systems discussion-engrossed discipline to only a more organizational and strategy-based approach [45]. All of these business tools were suggested in conjunction with an EA framework for planning as well as an EA methodology as an arm for the governance and implementation of strategic goals [13,23].…”
Section: Strategic Practicesmentioning
confidence: 99%